Heijunka-levelling customer orders: a systematic literature review - Meryem Boutbagha; Laila El Abbadi (International Journal of Production Management and Engineering)
Heijunka is the central concept of the Toyota Production System which aims to maintain both flexibility and stability of the production system by producing the same quantity of products every time interval (a day, a shift, an hour, etc.). This study is a systematic literature review whose objective is to give an idea about the most important research areas regarding this concept and to propose an agenda for further research. A total of 60 articles were reviewed using specified inclusion and exclusion criteria. The review showed that heijunka received little attention in the academic literature and disclosed the existence of three main research topics, namely: Implementation of heijunka and its benefits, Heijunka-related problem-solving using optimization, and Heijunka and Industry 4.0 technologies. This review could have some limitations related to the number of reviewed articles. It is possible that, unintentionally, some important articles haven’t been included.